SAT0222 BIIB059, a monoclonal antibody targeting BDCA2, shows evidence of biological activity and early clinical proof of concept in subjects with active cutaneous le. (15th June 2017) - Furie, R; Werth, VP; Merola, JF; Reynolds, TL; Stevenson, L; Wang, W; Smirnakis, K; Barbey, C; Musselli, C; Werneburg, B; Rabah, D; Franchimont, N
Abstract : Background: Type I interferons (IFN-I) are central to the pathogenesis of systemic lupus erythematosus (SLE). BDCA2 is a plasmacytoid dendritic cell (pDC)-specific receptor that, upon engagement, inhibits the production of IFN-I and other inflammatory mediators. Targeting BDCA2, therefore, represents an attractive therapeutic strategy for inhibiting pDC-driven inflammation that is such a key feature of SLE pathogenesis. BIIB059, an investigational anti-BDCA2 humanized monoclonal antibody, has been shown to engage BDCA2, and this interaction leads to BDCA2 internalization and the consequent in vitro inhibition of TLR-induced IFN-I production by pDCs (Pellerin 2015). Objectives: This first-in-patient study aimed to assess safety, tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) effects and clinical activity of BIIB059 in adult SLE patients with active cutaneous lupus (CLE) following administration of a single BIIB059 dose. Methods: A Phase 1b randomized, double-blinded, placebo controlled, multicenter clinical trial was conducted in 12 adult SLE subjects (meeting 1997 ACR criteria) with active cutaneous manifestations (including acute, sub-acute and/or chronic cutaneous forms of cutaneous lupus erythematosus (CLE)). Subjects received a single IV administration of either BIIB059 20mg/kg (n=8) or placebo (n=4). A panel of IFN-responsive genes (IRG) was assessed from whole blood by qPCR at baseline and several post-dose time points. Skin biopsies from active lesions were obtained and evaluated at baseline and week 4 for IFN-regulated proteins, including MxA and IFITM3 using quantitative immunohistochemistry. CLE disease activity was assessed using the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI), and safety data, including adverse events (AEs) and laboratory tests, were also collected. Results: Most SLE subjects had high IRG signatures in the blood. Skin biopsies demonstrated features of inflammation consistent with active CLE, including elevated expression of MxA and other IFN-regulated proteins. A single dose of BIIB059 decreased the expression of IRG in blood and MxA and IFITM3 proteins in the skin in most patients. CD45+ cells were reduced in skin biopsies of BIIB059-treated patients. The reduction in inflammatory cells as well as MxA and IFITM3 expression at week 4 correlated with improvement in CLASI activity score at multiple timepoints post-dose. BIIB059 was generally well tolerated with no discontinuations due to AEs. The incidence of AEs was similar between BIIB059- and placebo-treated SLE subjects, and most AEs were mild or moderate in severity. Conclusions: A single dose of BIIB059 resulted in inhibition of the IRG in peripheral blood and MxA and IFITM3 expression in lesional skin of SLE subjects, consistent with BIIB059's proposed mechanism of action. The clinical and biomarker data together confirm the role of human pDCs in the pathogenesis of SLE, and support further development of BIB059 in SLE. Disclosure of Interest: R. Furie Consultant for: Biogen, V. Werth Grant/research support from: Biogen, Consultant for: Biogen, J. Merola Grant/research support from: Biogen, Consultant for: Biogen, AbbVie, Amgen, Eli Lilly, Novartis, Pfizer, Janssen, Mallinckrodt, Momenta, Speakers bureau: AbbVie, Eli Lilly, T. Reynolds Shareholder of: Biogen, Employee of: Biogen, L. Stevenson Shareholder of: Biogen, Employee of: Biogen, W. Wang Shareholder of: Biogen, Employee of: Biogen, K. Smirnakis Shareholder of: Biogen, Employee of: Biogen, C. Barbey Shareholder of: Biogen, Employee of: Biogen, C. Musselli Shareholder of: Biogen, Employee of: Biogen, B. Werneburg Shareholder of: Biogen, Employee of: Biogen, D. Rabah Shareholder of: Biogen, Employee of: Biogen, N. Franchimont Shareholder of: Biogen, Employee of: Biogen